2021
DOI: 10.1155/2021/6678901
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Colistin-Resistant Escherichia coli in Retail Meat from Local Vietnamese Markets

Abstract: The spread of drug-resistant bacteria via food has contributed to the dissemination of resistant bacteria among humans. However, the status of food contamination with resistant bacteria, particularly the quantitative level of resistant bacteria in food, has not yet been well elucidated. In this study, the abundance of colistin-resistant Escherichia coli in meat samples was quantified to understand the origin of the contamination of meat available in local Vietnamese markets. Fifteen samples each of chicken and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…These results suggested that the origins of MDR E. coli isolated from clinical settings in Vietnam differed markedly. It is possible that they have originated from raw meat and shellfish [ 2 ], retail meats [ 4 , 6 ] and shrimp [ 5 ], hospital wastewater [ 6 ], backyard chicken farms [ 7 ], fecal sludge and soil [ 8 ], retail chicken carcasses [ 9 ], young dairy calves [ 10 ], urban rodents [ 5 ], and fish gut contents [ 11 ]. Because of their heterogeneity, the eradication of MDR E. coli from hospitals and environments is more challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that the origins of MDR E. coli isolated from clinical settings in Vietnam differed markedly. It is possible that they have originated from raw meat and shellfish [ 2 ], retail meats [ 4 , 6 ] and shrimp [ 5 ], hospital wastewater [ 6 ], backyard chicken farms [ 7 ], fecal sludge and soil [ 8 ], retail chicken carcasses [ 9 ], young dairy calves [ 10 ], urban rodents [ 5 ], and fish gut contents [ 11 ]. Because of their heterogeneity, the eradication of MDR E. coli from hospitals and environments is more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the distribution of antimicrobial resistance (AMR) genes in MDR E. coli isolated from clinical settings in Vietnam and the correlation between these genes and MDR phenotypes. To date, drug resistance genes have been analyzed in E. coli isolated from raw meat and shellfish [ 2 ], retail meats [ 3 , 4 ] and shrimp [ 5 ], hospital wastewater [ 6 ], backyard chicken farms [ 7 ], fecal sludge and soil [ 8 ], retail chicken carcasses [ 9 ], young dairy calves [ 10 ], urban rodents [ 5 ], and fish gut contents [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have documented the presence of antibiotic-resistant bacteria in products such as meat, fish, shellfish, and dairy. These bacteria may also be present on common market tools, such as scales, slicers, refrigerators, and, of course, cell phones used by vendors [21,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The carriage of MGCB by birds could result in the cross-contamination of poultry meat and associated products by these organisms during slaughter, processing, packaging, and selling. Studies have reported the presence of mcr-gene-harbouring organisms in poultry meats obtained from butchers/slaughterhouses/retail markets/supermarkets in China [57,[105][106][107][108][109] (Table S1), India [110], Bangladesh [110], Nepal [69][70][71], Türkiye [111,112], Pakistan [8], Vietnam [84,[113][114][115][116][117][118][119], Indonesia [55], Malaysia [54,120], Iraq [121], Laos [87,122], Tunisia [74], Algeria [123], Egypt [77][78][79], Brazil [124,125], the Dominican Republic [126], and Russia [127]. Worst of all, the storage temperature does not halt the exchange of mcr genes among meat-contaminating organisms since poultry meats stored at 4 • C, 25 • C, and 37 • C were conducive to the rapid exchange of mcr-1 between Salmonella and E. coli [5].…”
Section: Poultry Meatmentioning
confidence: 99%